INVENTARISASI MAKANAN ADAT DI NAGARI LUBUK ALUNG KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Vicky, Vicky; Baidar, Baidar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2016)
The purpose of this study was (1) Type custom events that still exist in Nagari Lubuk Alung are: (a) After marriage customs, (b) Events mancaliak child, (c) Events kikahan (d) After the circumcision apostles (e) Events Batagak home (f) Events Batagak prince and (g) Events after the death. As for (2) The menu is presented is in the form of staple food rice, side dishes are beef rendang, kalio meat, curry goat, curry chicken and sour padeh fish, vegetables namely goulash Cubadak and goulash tauco, and parabuang namely lapek bugih and rice kunyik, drinks are water, tea and coffee. (3) Recipe food traditional events in general white rice, side dishes, vegetables and pastries. Spices are used such as onion, garlic, cayenne pepper, turmeric, ginger, marica, bay leaves, lemon grass, galangal. Mechanical processing by boiling, steaming, butter up, sauteing and frying. (4) How to serve food is a way batatiang, where batatiang is serve food prepared on the one hand, this food is usually prepared for two to three servings in one hand.Keywords: Inventory, traditional food